Pengaruh Jumlah Jam Belajar dan Fasilitas Belajar terhadap Hasil Belajar Matematika Siswa SMP Negeru 4 Ajangale - Sumardin Raupu (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2018)
Abstract:The type of this research is expo facto research with the aims to determine whether the number of hours study and learning facilities affects to the student learning outcomes of mathematics in grade VIII SMP Negeri 4 Ajangale, Bone. The samples were taken in this research are 60 students from class VIII.A and VIII.B Lesson Year 2017/2018 by Cluster Random Sampling. The conclusion of this research is the number of student learning hours fall into enough category; Student learning facilities fall into less category and the student learning outcomes of mathematics into high category. The number of hours studied by observing the learning facility variables positively affects the student learning outcomes of mathematics with a value of R2 is 0.142. The learning facilities by observing the variable of learning hours did not positively affect the student learning outcomes of mathematics with the value of R2 is 0,005. The number of learning hours and learning facilities together positively influenced to the st dent learning outcomes of mathematics with the value of R2 is 0.154.Abstrak:Jenis penelitian ini adalah ekpost facto dengan tujuan untuk mengetahui pengaruh jumlah jam belajar dan fasilitas belajar terhadap hasil belajar matematika siswa kelas VIII SMP Negeri 4 Ajangale Kabupaten Bone Sulawesi Selatan. Jumlah sampel sebanyak 60 orang dari kelas VIII.A dan VIII.B Tahun Pelajaran 2017/2018. Sampel dipilih menggunakan Cluster Random Sampling. Kesimpulan dari penelitian ini yaitu, jumlah jam belajar siswa cukup, fasilitas belajar kurang, hasil belajar matematika siswa kategori tinggi. Jumlah jam belajar dengan memperhatikan variabel fasilitas belajar berpengaruh positif terhadap hasil belajar matematika siswa dengan R2 sebesar 0.142. Fasilitas belajar dengan memperhatikan variabel jumlah jam belajar tidak berpengaruh positif terhadap hasil belajar matematika siswa dengan R2 sebesar 0.005, Jumlah jam belajar dan fasilitas belajar secara bersama-sama berpengaruh positif terhadap hasil belajar matematika siswa dengan R2 sebesar 0.154.